Utility of bronchoscopy in immunocompromised paediatric patients: Systematic review. (April 2020) - Gonski, Kate; Cohn, Richard; Widger, John; McMullan, Brendan
Abstract: Purpose: The objective of this study was to describe the diagnostic yield and safety of bronchoalveolar lavage (BAL) in the evaluation of pulmonary lesions in immunocompromised children. Methods: We conducted a systematic review of literature published during the past 20 years, searching Medline, Medline EPub, EMBASE, and Scopus. Studies included involved paediatric patients (<18 years) on treatment for an oncological diagnosis or other immune compromise who underwent BAL for evaluation of pulmonary lesions. Only English language publications were included. Results: In all, 272 studies were screened and 19 included. All were observational studies with moderate (11/19) or serious (8/19) risk of bias. BAL yielded a potential pathogen in 43% of cases (496/1156). Two papers reported improved diagnostic yield with early BAL (less than 3 days of presentation). A change in patient management after BAL was reported in 53% of cases (275/519). Adverse events were reported in 19% of cases following BAL (193/993) but were generally mild with no procedure-related mortality reported. Conclusion: BAL appears to be useful for evaluation of pulmonary lesions in immunocompromised children with generally acceptable safety, though included studies had at least moderate risk of bias. Future prospective studies may provide more definitive estimates of benefit, timing and risk of BAL in this population.